EXAMINING DIFFERENT TECHNOLOGY AREAS IN SPORTS IN THE ATHLETE MENTAL HEALTH DIMENSION: Received: 28th November 2024 Revised: 7th December 2024, 10th December 2024 Accepted: 5th December 2024 - Akyol, Betül; Öztürk, Onur (PEOPLE: International Journal of Social Sciences, 2024)
Sports technologies have been in constant ’change and development’ since the day they first emerged until today. With each passing year, sports technologies develop by taking reference from each other through new technologies. With the development of sports technologies, generations are encountering more ’new and advanced’ technologies every day. Sports have an important place in protecting the physical and psychological health of individuals. Mental health has an important place in sports as well as physical health. In this respect, the aim of the current research is; It is aimed to examine different technology areas in sports in terms of mental health. As a data collection tool for this purpose; For Turkish sources, DergiPark, Higher Education Institution National Thesis Center (YÖKTEZ) and Google Scholar, and for English sources, in Web of Science and PubMed databases, with the keywords "Sports Technology", "Sports Mental Health", "Sports Entertainment" and "Technology Addiction". scanning has been done. As a result of the research; It is seen that technology in sports is used for different purposes such as ’entertainment, exercise and performance sports’. In some cases, the use of technology for more equipment or time than necessary reveals that it can create technology addiction in individuals and negatively affect their mental health. On the other hand, it is thought that conscious technology users can turn their current sports/exercises into productive and entertaining ones with sports technologies developed for different purposes. In this respect, as with all newly developing technologies, it has been concluded that determining the needs well and being a conscious sports technology user while using these technologies is important for mental health.